FEATURES OF RUSSIAN PHONETICS: PRONUNCIATION DIFFICULTIES FOR FOREIGN LEARNERS - Khalima Rinatovna Khakimova; Farrukh Bakhramovich Khakimov (World Scientific Research Journal, 2025)
This article examines the main phonetic difficulties encountered by foreign learners when studying Russian as a second language. The focus is placed on stress, vowel reduction, the system of hissing consonants, and palatalization. Each of these aspects is analyzed in detail with reference to typical learner errors and their underlying causes. The research is based on comparative phonetic analysis, observation of foreign students’ speech, and classroom experiments. The article also reviews teaching techniques that can help reduce pronunciation difficulties and evaluates the role of modern technologies in the development of pronunciation skills. The findings confirm that systematic phonetic training, supported by technological and methodological innovations, is essential for improving the pronunciation skills of foreign students.